Incentives to Innovate and the Decision to Go Public or Private - Ferreira, Daniel; Manso, Gustavo; Silva, André C. (Review of Financial Studies, 2014)
We model the impact of public and private ownership structures on firms' incentives to invest in innovative projects. We show that it is optimal to go public when exploiting existing ideas and optimal to go private when exploring new ideas. This result derives from the fact that private firms are less transparent to outside investors than are public firms. In private firms, insiders can time the market by choosing an early exit strategy if they receive bad news. This option makes insiders more tolerant of failures and thus more inclined to invest in innovative projects. In contrast, the prices of publicly traded securities react quickly to good news, providing insiders with incentives to choose conventional projects and cash in early.